Research on Calculation Methods of Building Envelope Thermal Characteristics - Farenyuk, Gennadiy; Filonenko, Olena; Datsenko, Volodymyr (International Journal of Engineering and Technology, 2018)
Building envelope functional performance largely depends on the temperature fluctuation range on the interior surface. The aim of the calculation is to ensure that building envelope has the necessary thermal characteristics, which ensure maintaining almost stable temperature on the interior surface of the construction, under the periodic changes of environmental parameters. The dynamic thermal characteristics can also be used in the calculation of: the internal temperature in a room; the daily peak power and energy needs for heating or cooling; the effects of intermittent heating or cooling, etc. Exact prediction of building envelope temperature conditions under periodic thermal effects allows avoiding thermal failures. Calculation methods in the Ukraine state construction standards are significantly simplified. Currently, with return to furnace heating and other kinds of periodic heating, international standard calculation method is more important and requires revising the Ukrainian normative base.
Keywords: density of heat flow rate; period of the variations; specific heat capacity; thermal resistance